Managerial ownership, board characteristics and stock price informativeness in Indonesia stock market: examination of the pre-IFRS and post-IFRS adoption periods / Dwi Astuti Rosmianingrum ...[et al.] - Rosmianingrum, Dwi Astuti; Arshad, Roshayani; Mohammed, Nor Farizal; Leo, Lianny (Universiti Teknologi MARA, 2022)
Publicly available information is mainly determined by firm-specific and market-wide information. When stock price changes are influenced more by firm-specific, the stock price synchronicity (SYNCH) is expected to be lower and vice versa. Financial reporting under the IFRS Standards is considered to have a higher quality than financial statements prepared under national accounting standards (GAAP). One of the pillars of good corporate governance is the existence of an effective internal mechanism such as board characteristics. This study examined the relationship between SYNCH and managerial ownership and board characteristics which included board size and board independence during the most comprehensive period of IFRS adoption in Indonesia covering the periods of pre-IFRS, transition and post- IFRS adoption. Using firms listed in the Indonesia Stock Exchange from 2007-2019, panel data regression analysis showed significant decrease in SYNCH after the adoption of IFRS. Other findings suggest that management and supervisory functions of the boards can be disrupted if there is larger board, and the presence of an independent board is seen as ineffective in increasing informativeness of stock price.